2014
DOI: 10.3892/etm.2014.2041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dysregulated miRNAs and their regulatory signature in glioma patients using the partial least squares method

Abstract: Using microarray data, the present study identified differentially expressed microRNAs (miRNAs) and evaluated their regulatory characteristics in high-grade glioma patients, with the aim to further the understanding into the underlying etiology of the condition. Previously, studies have generally implemented regression or variance analysis, which ignores various background biological factors. However, in the present study, analysis was performed with microarray data collected from the Gene Expression Omnibus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…were significantly increased in patient tumor samples and its high expression was associated with a reduction in survival time (11). Another study identified that the low expression of miR-1908 predicted a poor prognosis in glioma (12). In addition, miR-1908 has also been associated with the prognosis of chordoma, hepatoma and melanoma (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…were significantly increased in patient tumor samples and its high expression was associated with a reduction in survival time (11). Another study identified that the low expression of miR-1908 predicted a poor prognosis in glioma (12). In addition, miR-1908 has also been associated with the prognosis of chordoma, hepatoma and melanoma (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…This approach enabled the identification of miRNAs whose expression levels were significantly altered in tumor tissue compared to peripheral brain tissue of the same patient, including miR-221, which was strongly up-regulated in GBM, and a set of brain-enriched miRNAs (miR-128, miR-181a, miR-181b, and miR-181c), which were down-regulated in GBM [32]. Very recently, a number of prognostic miRNA signatures have been reported for GBM [3335, 15, 36, 37, 1820, 38, 39]. We compared these signatures with our signature in terms of complexity, independent validation, and the approach used for identification of the signature.…”
Section: Discussionmentioning
confidence: 99%
“…For data sets with moderate dimensionality such as miRNA microarray data sets with typically a few hundreds of miRNAs expressed, the number of features contained in a signature should be of low complexity and in the range of smaller than 10. From the above cited studies, only five extracted a miRNA signature with low complexity that have been subsequently validated in an independent cohort [15, 37, 1820]. Cheng et al [15] focused on MGMT promoter methylation positive tumors only and defined a 5-miRNA signature that was validated in an appropriate subset of the so-called Chinese Glioma Genome Atlas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations